Investigation of Planing Hull Resistance Calculation Using Smoothed Particle Hydrodynamics - Andi Trimulyono; Muhammad Fajar Nuralam; Deddy Chrismianto; Samuel; Imam Pujo Mulyatno; Muhammad Iqbal (International Journal of Marine Engineering Innovation and Research, 2025)
Over the decades, advancements in computer technology have significantly contributed to the development of numerical methods, including computational fluid dynamics (CFD). CFD encompasses two primary approaches: mesh-based and mesh-free methods. While mesh-based methods are well-established and widely used for analyzing free-surface flows, such as ship resistance, mesh-free methods like smoothed particle hydrodynamics (SPH) have gained traction in real-world engineering applications. Despite its growing use, limited research has explored the application of SPH to ship resistance analysis. This study investigates the total ship resistance of a planing hull using the open-source SPH solver DualSPHysics. The research focuses on analyzing spray patterns and complex flow dynamics around the hull. DualSPHysics typically employs dynamic boundary conditions (DBC) as its standard boundary definition method. However, this study utilizes an advanced implementation of DBC, known as Modified Dynamic Boundary Conditions (mDBC), in conjunction with Project Chrono for enhanced simulation accuracy. The results demonstrate that SPH provides acceptable accuracy when compared to the Strip theory approach. Additionally, key parameters such as total force, sinkage, and trim are effectively reproduced using Project Chrono. This research highlights the potential of SPH, particularly with advanced boundary conditions, for ship resistance analysis and contributes to the growing body of knowledge in this field.